KELUARGA BERENCANA PERSPEKTif FIQIH EMPAT MAZHAB: Studi Analisis Tentang Tahdid Al-Nasl dan Tandzim Al-Nasl - Abdul Hakim; Imam Syafi'i (Al-Maslahah : Jurnal Ilmu Syariah, 2021)
Suggested have children is one of the main motivations in the process of marriage, for she is the successor relay struggle both parents in their life in the world and the Hereafter later. This is also confirmed by religion in the maqashid al-shari'ah (the main purpose of the Shari'ah), where one of the maqashid is hifz al-Nasl (keep offspring). In Indonesia, there is one program known as Family Planning. Action to tahdid and tandzim al-Nasl are applied with regard to three aspects, namely the purpose, objective aspects and aspects of the way or method. Then, based on the agreement of the scholars, either by using `practice coitus interruptus, drugs or other means. And based on the principles that need to be considered in the concept tahdid and tandzim al-Nasl, where the principles were the basis for the permissibility do tahdid and tandzim al-Nasl, in accordance with the limits set by the scholars'.